Proposing a comprehensive framework for needs analysis in ESP – on the integrality of needs analysis in Business English course design - ROMANOWSKI, PIOTR (Glottodidactica, 2017)
The present paper discusses the importance of needs analysis in ESP. By delving into different theories, the author’s overall objective is to scrutinize a wide spectrum of existing frameworks that would lead to a single, comprehensive model for needs assessment. The impact of the said approaches on course design is underlined with the particular example of Business English. Ultimately, the author unveils a framework which could serve as a basis for syllabus design in all types of ESP courses.